Pengaruh Ukuran Butir Pasir Besi dan Volume Air Laut pada Absorber Type Fins Solar Destilation terhadap Produktifitas Air Tawar - Anggara, Mietra; Widhiyanuriyawan, Denny; Sasongko, Mega Nur (Jurnal Rekayasa Mesin, 2016)
The needs of clean water is especially increased for the living in coastal. Because of that, a simple equipment and low cost operation is needed. Distillation is a method to convert sea water to fresh water by using solar energy. Various research on absorbent plate solar still has been done to increase productivity and efficiency of distillation. In the study, fins absorbent plate was tested with iron ore grain size variation of 0,125 cm, 0,250 cm and flat absorbent plate with iron ore grain size variation of 0,125 cm. The volume of salt water in the basin is also varied of 1, 2, and 4 liters. The results shown that the fin absorbent plate with iron ore size of 0.125 cm and the volume of 1 liter have the highest freshwater productivity and efficiency of 3,7 l/m day and53,55%, respectively. The daily sun radiation of 16,071 MJ/m .day. The quality of resulted fresh water has fulfilled the standard for drinking water, hence it is consumable.